Identifying facilitators and barriers to integrated and equitable care for community-dwelling older adults with high emergency department use from historically marginalized groups - Krystal Kehoe MacLeod; Karyle Nama Flores; Kavish Chandra (BMC, 2023)
Abstract Background High rates of emergency department (ED) use by older adults persist despite attempts to improve accessibility of appropriate and comprehensive care. Understanding the drivers of ED visits from the perspective of older adults from historically marginalized groups could help reduce ED use by patients with needs that are preventable or could have been treated in a more appropriate setting. This interpretivist, feminist study aims to explore the unmet care needs of older adults (age 65 +) with high ED use and belonging to historically marginalized groups to better understand how social and structural inequities reinforced by neoliberalism; federal and provincial governance structures and policy frameworks; and regional processes and local institutional practices, shape the experiences of these older adults, particularly those at risk of poor health outcomes based on the social determinants of health (SDH). Methods/design This mixed methods study will employ an integrated knowledge translation (iKT) approach, starting with a quantitative phase followed by a qualitative phase. Older adults self-identifying as belonging to a historically marginalized group, having visited an ED three or more times in the past 12 months, and living in a private dwelling, will be recruited using flyers posted at two emergency care sites and by an on-site research assistant. Data obtained through surveys, short answer questions, and chart review will be used to compile case profiles of patients from historically marginalized groups with potentially avoidable ED visits. Descriptive and inferential statistical analyses and inductive thematic analysis will be conducted. Findings will be interpreted using the Intersectionality-Based Policy Analysis Framework to identify the interconnections between unmet care needs, potentially avoidable ED admissions, structural inequalities, and the SDH. Semi-structured interviews will be conducted with a subset of older adults at risk of poor health outcomes based on SDH, family care partners, and health care professionals to validate preliminary findings and collect additional data on perceived facilitators and barriers to integrated and accessible care. Discussion Exploring the linkages between potentially avoidable ED visits by older adults from marginalized groups and how their care experiences have been shaped by inequities in the systems, policies, and institutions that structure health and social care provision will enable researchers to offer recommendations for equity-focused policy and clinical practice reforms to improve patient outcomes and system integration.